Effects of Diluent pH on Enrichment and Performance of Dairy Goat X/Y Sperm - He, Qifu; Wu, Shenghui; Huang, Ming; Wang, Ying; Zhang, Kang; Kang, Jian; Zhang, Yong; Quan, Fusheng (Frontiers in Cell and Developmental Biology, 2021)
In this paper, on the basis of the differences in the pH of the diluent dairy goat semen on X/Y sperm motility, an X/Y sperm enrichment study was conducted to establish a simple and effective method for gender control in dairy goats. Dairy goat semen was diluted using different pH dilutions and was incubated. Then, the X/Y sperm ratio in the isolated upper sperm was determined using the double TaqMan qPCR method. The internal pH change pattern of sperm cells at different pH dilutions was measured using BCECF-AM probe, and the functional parameters of the isolated sperm were tested with the corresponding kit. Next, an in vitro fertilization test was conducted using isolated spermatozoa and oocytes to determine their fertilization rates, the percentages of female embryos, and the expression of genes related to developing potentially fertilized embryos. Results showed that the percentages of the X sperm cells in the upper sperm layer were 67.24% ± 2.61% at sperm dilution pH of 6.2 and 30.45% ± 1.03% at sperm dilution pH of 7.4, which was significantly different from 52.35% ± 1.72% of the control group (pH 6.8) (P < 0.01). Results also showed that there is a relationship between the external pHo and internal pHi of sperm cells. Furthermore, the percentages of female embryos after the in vitro fertilization of the isolated upper sperm with mature oocytes at pH 6.2 and 7.4 were 66.67% ± 0.05% and 29.73% ± 0.04%, respectively, compared with 48.57% ± 0.02% in the control group (pH 6.8). Highly significant differences occurred between groups (P < 0.01). Additionally, no significant difference was observed during the expression of genes related to embryonic development between the blastocysts formed from sperm isolated by changing the pH of the diluent and the control sperm (P > 0.05). Therefore, this study successfully established a simple and effective method for enriched X/Y sperms from dairy goats, which is important for regulating the desired sex progeny during dairy goat breeding and for guiding dairy goat production.